Building Process of a CD-Rom Aiming To Help Students, From 11 To 16 Years Old, To Write School Newspapers - Tomé, V. (Conference Proceedings Book of International Conference on Education Innovation, Technology and Research on Education, 2006)
This paper aims to explain the building process of the Multimedia CD-Rom "Let’s produce school newspapers". It has the purpose of helping 11 to 16 years old pupils, as well as the teachers, in school newspapers production. It uses text, photos and film bearing in mind inserting the present educational tendencies, all over the world towards media education. This paper explains the technical and technological options we have followed, as well as the pedagogical ones, which support this multimedia application.